2021
DOI: 10.1002/jcph.1925
|View full text |Cite
|
Sign up to set email alerts
|

A Target‐Mediated Drug Disposition Model to Explain Nonlinear Pharmacokinetics of the 11β‐Hydroxysteroid Dehydrogenase Type 1 Inhibitor SPI‐62 in Healthy Adults

Abstract: SPI-62 is a selective and potent small-molecule inhibitor of 11β-hydroxysteroid dehydrogenase type 1 (HSD-1). SPI-62 has demonstrated substantial and complex nonlinear pharmacokinetics (PK) in humans that is characterized by unusually low plasma exposures at low doses; dose-dependent This article is protected by copyright. All rights reserved. 2 volume of distribution; nonlinear PK following the first dose and dose-proportional PK at steady state; as well as unusually high accumulation ratios at low doses. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 28 publications
(100 reference statements)
4
22
0
Order By: Relevance
“…22 However, the observed BMS-823778 C max value was only 19 ng/mL in the 5-mg dose group and was undetectable in the 0.5-mg dose group. 22 Results from the FIH MAD study showed that the nonlinear pharmacokinetics of BMS-823778 at low doses observed on day 1 disappeared after repeated doses, as reflected by the dose-proportional pharmacokinetics across all doses on day 14 22 ; this unusual phenomenon was also observed for ABT-384, 11 SPI-62, 32 and MK-0916. 23 Similarly, BMS-823778 accumulation ratios were also dose dependent, with unusually high values for the low-dose groups.…”
Section: Example 4 Bms-823778mentioning
confidence: 89%
See 4 more Smart Citations
“…22 However, the observed BMS-823778 C max value was only 19 ng/mL in the 5-mg dose group and was undetectable in the 0.5-mg dose group. 22 Results from the FIH MAD study showed that the nonlinear pharmacokinetics of BMS-823778 at low doses observed on day 1 disappeared after repeated doses, as reflected by the dose-proportional pharmacokinetics across all doses on day 14 22 ; this unusual phenomenon was also observed for ABT-384, 11 SPI-62, 32 and MK-0916. 23 Similarly, BMS-823778 accumulation ratios were also dose dependent, with unusually high values for the low-dose groups.…”
Section: Example 4 Bms-823778mentioning
confidence: 89%
“…Interestingly, the nonlinear pharmacokinetics exhibited after the first dose disappeared after repeated doses, as reflected by the superimposed plots on day 7 across In these 2 dose groups, SPI-62 was given as single dose first (day 1), followed by a 6-day washout (days 1 to 6), and then 14 days QD doses (days 7 to 20). Figure 3a-c was adapted from Wu et al 32 Figure 3d was adapted from Bellaire et al 21 all doses evaluated (Figure 2a). Figure 2b shows that the accumulation ratio, calculated as the C max of ABT-384 on day 7 over the C max of ABT-384 on day 1, was >41 in the 1-mg dose group, 24.2 in the 2-mg dose group, 11.3 in the 4-mg dose group, and dropped to 1 to 2 in the higher dose groups.…”
Section: Example 1 Abt-384mentioning
confidence: 99%
See 3 more Smart Citations